Community-based active tuberculosis case finding using a symptom-based screening tool in the Volta Region, Ghana. (January 2021) - Ntow, George Edward; Kweku, Margaret; Aninagyei, Enoch; Duedu, Kwabena O.
Highlights: Symptom-based screening tools are critical in frontline screening of tuberculosis, and the National Tuberculosis Control Programme in Ghana has over the years developed, used and improved the current tool. Active case finding in communities using two strategies, house-to-house visitation and community durbars, was evaluated with use of the symptom-based screening tool. House-to-house active case searching for tuberculosis proved to be the most effective for active case finding. The prevalence of tuberculosis in the study communities in Ghana was 15 per 100, 000 population. A Mycobacterium tuberculosis strain resistant to rifampicin was detected from the active community case search. Abstract: Background: Early tuberculosis case detection is important for early commencement of treatment to improve treatment outcomes and also to prevent community spread of the disease. However, there is a paucity of data in Ghana on the efficiency of the symptom-based screening tool (SBS tool) to detect Mycobacterium tuberculosis in the communities. Therefore, this study assessed the usefulness of the SBS tool for community-based active case finding in the Volta Region of Ghana. Methods and materials: This cross-sectional study used house-to-house and durbar screening approaches for active tuberculosis (TB) case searching from six communities, three each from the Ketu South (high TB risk) and Akatsi North (low TB risk) districts in the Volta Region of Ghana. Random eligible participants were screened with the SBS tool to identify presumptive TB cases. One sputum sample was collected from each person with presumptive TB for detection of M. tuberculosis by the GeneXpert real-time technique. Results: A total of 1, 025 people were screened from a population of 40, 462, from which 332 (32.4%) were presumed to have M. tuberculosis infection. Of the 332 presumptive TB cases, 63.9% were obtained through house-to-house screening, while 36.1% were obtained through community durbar screening. Six M. tuberculosis -positive cases (with one rifampicin resistance) were detected by house-to-house screening but not from community durbar samples, yielding an overall prevalence of 15 per 100, 000 population. Among TB symptoms screened and analysed, association existed only between night sweat and TB case detection ( χ 2 = 3.9, P = 0.049). Conclusion: Although cumbersome and capital intensive, community-based active case searching through house-to-house screening using the SBS tool proved effective in detecting M. tuberculosis in the communities.